5 Temporal changes in percutaneous coronary intervention in the elderly. (7th October 2015) - Johnston, P; Mailey, J; Linden, K; McKavanagh, P
Abstract : Introduction: We previously reported PCI outcomes in the elderly (age ≥80) over the 2 year period 2003–4. Since then the unit has introduced routine primary PCI and TAVI. This re-audit assessed the impact of these changes on our practice and outcomes. Methods: All elderly PCI patients in 2014 were identified using the trust PCI database and 90 day outcomes obtained from the Northern Ireland electronic care record. Results: There were 257 PCIs in 241 elderly patients; 90 day outcome data was available for 239 patients. Demographics, presentation and outcomes are compared with the previous audit (which reported in-hospital and 1 year outcomes) in this Table 1 . In 2014 15.1% of our PCIs were in elderly patients (compared with 10.4% nationally, BCIS 2013 audit figures). This represents a 6 fold increase in our elderly PCI rate (2.5% vs 15.1%) over 10 years. This has been driven by a substantial increase in AMI angioplasty in the elderly (1.8% vs 33.5% of elderly PCIs). In spite of this high risk population, in-hospital mortality remained relatively low. Mortality for ≥ 80 year old patients was 15/257 (5.8%) compared with 33/1441 (2.3%) for those <80 years. Of the 15 in-hospital deaths, 12 presented with acute MI and 3 had undergone rotablation (2 pre-TAVI and one with a NSTEMI). At 90 days mortality for ≥80 year old patients was 23/255 (9.0%); 5 of the 8 deaths following discharge were non-cardiac. At 90 days a further 5 (2.0%) patients suffered a non-fatal MI and 8 (3.1%) patients suffered a CVA. Conclusion: The significant increase in elderly PCI observed over this 10 year period appears to be justified by outcome measures.